Always, Abigail - Cavanaugh, Nancy J. (Naperville, Illinois : Sourcebooks Jabberwocky, 2014)
Sixth grader Abigail, assigned a different homeroom than her two best friends and made only the alternate on the pom-pom squad, learns a lot about popularity and true friendship when paired with unpopular Gabby for a year-long "Friendly Letter Assignment."
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Popularity -- Fiction